(3bVjI GdfhQ GdeMeOi (B: (3CUhdgG GdJGQjNjI h BKGQgG GdOjfjI Hjf GdacQ GdTjYj h GdUhaj MJi fgGjI GdbQf GdSGHY GdgLQj (B: s (3OGQSI JMdjdjI fbOjI ebGQfI (B/ s - (3egG SejQ eMeO eUHGMs; (3YHOGdMejO YHOGdefYe eOchQ (B: s ((3GdbGgQI (B: s (3egG SejQ eMeO eUHGM (B: s, 2012)
(3jgOa Edi OQGSI JaUjdjI ddfhQ GdeMeOj ceUWdM NGU XgQ dOi GdTjYI h GdUhajI h HjGf OdGdJg GdJaUjdjI GdNGUI dOi cd efgeG eY eMGhdI GSJcTGa YdGbGJ GdJCKjQ h GdJCKQ ShGA GdeJHGOdI ajeG HjfgeG Ch JCKjQ GdCacGQ GdNGQLI Yf GdhSW GdESdGej YdjgeG(B. (3h Ydj Cj eSJhi Je gPG GdJCKjQ? gd cGf Ydi eSJhj(B: (3GdCacGQ(B: (3Ce GdeUWdMGJ(B: (3Ce Cf GdeUWdMGJ GdeCNhPI ef Cgd Gdedd h GdfMd GdCNQi bO aQZJ ef eVGejfgG GdSGHbI h MedJ eVGejf CNQi ESdGejI? aGdHMK EPf OQGSI JMdjdjI ebGQfI dcd ef GdacQ GdTjYj h GdUhaj ajeG jJYdb HbVjI GdfhQ GdeMeOj dOj cd efgeG eY YQV BQGFge ddfbO Ydi VhA GdcJGH h GdSfIs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI OGQ GdYdhe (B- (3bSe GdadSaI GdESdGejIs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdMVQI GdLGeYIs; (3GdMbjbI GdeMeOjI s; (3GdfhQ GdeMeOi s